Physical and Chemical Properties of Coal in the Process of its Hydrotransportation - Biletskyi, V. S.; Desna, N. A.; Orlovskyi, V. M.; Biletskyi, V. V. (VÚRUP, 2024)
In the article, in the laboratory and field experiments an evolution of surface physical and chemical properties of coal was traced in the process of its hydrotransportation. Laboratory imitation of the coal hydrotransportation process was effected by mixing water-and-coal hydraulic mixture F : L = 1:1 in the turbulent mode during 48 hours that is equivalent to pulp movement in the coal pipeline at the rate of 2 m/s for the distance of 350 km. High-volatile coal with a grain size of 0-2 and 0-0.1 mm Ad=8.6%, Vdaf = 37.5%, Ro = 0.70% was used as the initial material. Disperse medium is distilled water, 0.2% solution Ca(OH)2 and 0.1% solution Na2SiO3. Before and after hydrotransportation, coal was researched by IR and UV spectroscopy methods. Oxidative-hydrolytic processes associated with addition of water to hydrophilic groups (carboxyl, carbonyl, etc.) and leaching of individual components into the liquid phase have been established. The reactions are intensified with the change in pH of the environment, that is, with the introduction of corrosion inhibitors of the coal pipeline. Field modelling of the hydrotransportation process of coking coal was performed on a hydrodynamic torus, which was a ring 3 m in diameter made of a steel pipe with an inner diameter of 202 mm, installed vertically. The ring rotated with a direct current motor. The ring coal pipe was filled with hydrocarbon pulp to 2/3 of the volume. The initial material is a balanced coal charge for coking from the Donetsk basin (Ad= 9.0%, Vdaf = 30.6 %, 𝑆𝑆𝑑𝑑𝑡𝑡= 2.2%, Ro = 0.21 %, grain size 6 - 0 mm). The distance of landfill transportation of the charge is 2.000 km. The initial charge was investigated by IR spectroscopy before and after hydrotransportation for 300, 1000, 2000 km. The surface ζ-potential of the coal material was determined for the charge before and after hydrotransportation. According to the evolution of IR spectra of the samples, the oxidation of the coal phase was established, which is most contrasted when comparing the spectra of the original coal and after hydrotransportation for 1000-2000 km. Changes in the spectra increase with the increase in the range of hydrotransportation. Significant changes in the shape of grains as a result of their rolling in the pipeline are already observed at the point of 450 km of hydrotransportation. Hydraulic transport leads to a significant increase in the ζ-potential of the coal surface. This confirms its hydrophilic behaviour in the process of hydro-transportation.
Keywords: coal; surface properties; hydraulic transport; molecular spectroscopy; laboratory experiment; field experiment